Anthony D'Avray (ed. and annotated in collaboration with Richard Pankhurst): The Nakfa Documents. The despatches, memoranda, reports and correspondence describing and explaining the Stories of the Feudal Societies of the Red Sea Littoral from the Christi - Bekele, Shiferaw (Aethiopica, 2002)
Review